2020
DOI: 10.1007/s10562-020-03247-3
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Decomposition Enhancement by Cs-Promoted Fe/Al2O3 Catalysts

Abstract: A range of Cs-doped Fe/Al2O3 catalysts were prepared for the ammonia decomposition reaction. Through time on-line studies it was shown that at all loadings of Cs investigated the activity of the Fe/Al2O3 catalysts was enhanced, with the optimum Cs:Fe being ca. 1. Initially, the rate of NH3 decomposition was low, typically < 10% equilibrium conversion (99.7%@500°C) recorded after 1 h. All catalysts exhibited an induction period (typically ca. 10 h) with the conversion reaching a high of 67% equilibrium conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Research and development of catalysts are done on precious metals, bimetallic materials, and metal oxides [38][39][40][41][42]. The bimetallic compound is proven to improve catalytic performance even though the manufacturing is complicated.…”
Section: Nh 3 Decompositionmentioning
confidence: 99%
“…Research and development of catalysts are done on precious metals, bimetallic materials, and metal oxides [38][39][40][41][42]. The bimetallic compound is proven to improve catalytic performance even though the manufacturing is complicated.…”
Section: Nh 3 Decompositionmentioning
confidence: 99%
“…In addition, both Pb 4f 7/2 (137.3 eV) and Pb 4f 5/2 (142.1 eV) peaks in PbPA-CsPbBr 3 are much closer to those in PbPA, suggesting the Pb atoms in PbPA-CsPbBr 3 originate from the PbPA framework instead of the residual Pb 2+ (Figure d) . A slight shift toward low binding energies for both Pb 4f and the adjacent P 2s after the conversion indicates the redistribution of electron density around the Pb and P atoms after the in situ perovskite formation (Figure e). , The ratio of CsPbBr 3 in the final PbPA-CsPbBr 3 was further estimated by inductively coupled plasma optical emission spectroscopy (ICP-OES) analysis (Figure S5). The molar ratio of Cs:Pb in CsPbBr 3 is 1:1, illustrating the reliability of this measurement .…”
Section: Resultsmentioning
confidence: 94%
“…30 A slight shift toward low binding energies for both Pb 4f and the adjacent P 2s after the conversion indicates the redistribution of electron density around the Pb and P atoms after the in situ perovskite formation (Figure 1e). 31,32 The ratio of CsPbBr 3 in the final PbPA-CsPbBr 3 was further estimated by inductively coupled plasma optical emission spectroscopy (ICP-OES) analysis (Figure S5). The molar ratio of Cs:Pb in CsPbBr 3 is 1:1, illustrating the reliability of this measurement.…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of XPS, FTIR, and TGA, it could be concluded that there were abundant OH groups over the Cs-doped catalysts. These OH groups might be generated by the deliquescence of Cs 2 O 2 and would occupy the active sites to decrease catalytic activity on N 2 O decomposition. , The weight loss above 700 °C was attributed to the loss of bulk lattice oxygen of Co 3 O 4 , and the theoretical weight loss from Co 3 O 4 to CoO should be approximately 6.6%. It was observed that 4Cs/Co 3 O 4 catalysts have only 4.9% weight loss due to the improved thermal stability of the Cs–O–Co structure.…”
Section: Resultsmentioning
confidence: 99%